Combustion chemistry of n-heptane/ethanol blends: a ReaxFF study. Issue 1 (2nd January 2021) - Liu, Yalan; Ding, Junxia
ABSTRACT: The effect of ethanol on n-heptane oxidation was studied using the reactive molecular dynamics (RMD) method. With different ethanol concentrations, simulations were performed under fuel-rich conditions from 2000 −2500 K. The results showed that ethanol addition had little effect on the n-heptane oxidation rate. However, the presence of ethanol inhibited the formation of major species (e.g. Ethylene and Formaldehyde) in different ways. The amount of C2 H4 during n-heptane oxidation was clearly greater than that during n-heptane/ethanol oxidation, indicating that the dissociation of ethanol (C2 H5 OH →C2 H4  + H2 O) was not an effective pathway to produce C2 H4 . Conversely, ethanol addition had a two-fold impact on CH2 O formation at high temperatures. Ethanol promoted the formation of the C2 H5 O radical, which was the main intermediate to produce CH2 O. However, ethanol addition reduced the amount of n-heptane in the system, lowered the rate of CH3 radical formation, and subsequently decreased CH2 O formation, consistent with previous experiments.